Sa pagpanaw ng kabiyak a grounded theory approach on the bereavement process of widowers from Sapian and Roxas City, Capiz. - Ochavo, Ma. Loulaine Glee H.
This research project studies how gender roles and social support affect the bereavement process of rural and urban widowers using the grounded theory approach . Nine respondents were asked to answer the Norbeck's Social Support Questionnaire (NSSQ) followed by an in-depth interview. By examining the NSSQ results and coded transcriptions, the researcher found out that concrete and emotional support was often given to widowers by family members, relatives, friends and neighbors. An important finding of this study also points to the social construction of the bereavement process of widowers which were largely shaped by the associated expectations of the gender roles hold by men and is reinforced by how network members laced their advice with heteropatriarchal values.